Hasil Pengabdian Masyarakat Latihan dan Perkenalan Bela Diri Praktis Di Sekotong Barat - Adi suriatno; Rusdiana Yusuf; Likman; Tiassari Janjang Suminar; Kokom Supryatnak (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Security and physical resilience are important aspects in everyday life that can increase feelings of security and self-confidence in facing various situations. The community service program entitled